(untitled) (Fiep Bulletin - online, 2020)
In the first half of the 1990s, tele dramaturgy remained, to a certain extent, following much of the path taken in previous years. The productions marked by the characterization of body meanings gained an even more important role, mainly due to the technological advances and the consolidation of the expansion of the telecommunications sector with the project led by the Brazilian Telecommunications Company (Embratel), which made possible the coverage network throughout the Brazilian territory.In this sense, the main objective of this article is to reflect on the role of Brazilian television drama, especially from the 1980s, regarding the new configurations of the “ideal body” and the construction of the so-called “health generation”. These reflections are important precisely because they represent a point of reference and a milestone in the growth of gyms and bodybuilding. Importantly, media (especially television) represented a unique space for the propagation of the “new” body, beauty and behavioral patterns to be followed by society. The exposure of the female body, for example, by the actresses in evidence translated the image that the cultural industry defined as the one that should be desired. The methods used were bibliographic and exploratory research, through the analysis of articles, books, videos, and other sources, whose approach is based on questions about body, cultural industry, teledramaturgy and cyber space.